Phaeurus antarcticus and its endophytic fungi: chemical diversity of a hidden pharmacy underneath the Antarctic Ocean - Santos, Gustavo Souza dos (2022)
Chapter I: The chemical profile and antibacterial, antiparasitic, and insecticidal activities of the seaweed P. antarcticus were investigated. The hexane extract (HX) and its fractions exhibited selective antibacterial activity against Staphylococcus aureus. Fractions HX-FC and HX-FD showed the highest antiparasitic activity against Leishmania amazonensis and Neospora caninum. The HX extract and the HX-FC fraction presented insecticidal potential against Aedes aegypti larvae. Through GC-MS analysis and the combination of multivariate statistical analyses (OPLS-DA) and the construction of molecular networks (GNPS), it was possible to annotate terpenes, steroids, fatty acids, and alcohols in the bioactive fractions. Chapter II: Using metabolomics techniques (UPLC-HRMS/1H NMR) and multivariate statistical analysis (PCA, OPLS-DA), the spatial variability of secondary metabolites of the seaweed P. antarcticus and the antibiofilm activity of extracts and fractions were evaluated against S. aureus resistant to methicillin-oxacillin (MRSA). The results revealed that the changes in the chemical profile were not site-specific and could be related to different life cycle stages of the collected algae. Porphyrins, terpenes, and carotenoids were annotated as discriminating compounds. Linoleic acid (1) and fucosterol (2) were isolated from the bioactive fractions and showed antibiofilm activity against MRSA. Chapter III: The extract and fractions of the fungus Penicillium purpurogenum were evaluated for antibacterial, antiparasitic, immunomodulatory, and photoprotective activities. The bioguided fractionation led to the isolation of six polyketides: 5,6,8-trihydroxy-4-(1\'-hydroxyethyl) isocoumarin (3), aspergillumarin A (4), aspergillumarin B (5), Berkeleyacetal C (6), sescandelin (7), and vermistatin (8). Compounds 3, 4, 7, and 8 presented photostability and photoprotective activities against UVB-UVA. Compounds 3, 6, 7, and 8 presented immunomodulatory activity by down-regulating the production of reactive oxygen species in PMA-stimulated human neutrophils without cytotoxic effects. Compound 6 presented leishmanicidal activity against amastigotes of L. amazonensis. Chapter IV: The chemical profile (UPLC-HRMS/1H NMR) and antibiofilm activity against MRSA of 21 fungal strains were investigated. Among them, the fractionation of the extract of the fungus Epicoccum nigrum led to the isolation of epicorazines A-B (9-10) and C (12) as well as a new terpenoid (11). Compound 9-12 exhibited antibiofilm activity against MRSA. Among these, compound 11 showed the highest inhibition of pre-biofilm formation and rupture of the formed biofilm. Given the global context, this work sought to obtain new biotechnological products, considering the United Nations Sustainable Development Goals. The results obtained provide new information about the chemotaxonomy and biotechnological potential of Antarctic marine organisms as producers of biomolecules of pharmaceutical interest, emphasizing the importance of bioprospecting for the conservation of understudied organisms.